Ethiopia : A Country Status Report on Health and Poverty, Volume 2, Main Report - World Bank (Washington, DC, 2012)
The Government of Ethiopia has recently confirmed its commitment to accelerate progress on maternal and child health outcomes. A reduction in child and maternal mortality rates is among the key objectives of the Ethiopia Poverty Reduction Strategy (PRSP) published in 2002. This strategy outlines the Government's key policy objectives and strategic options for the next five years. One key PRSP strategic option for reducing maternal and child mortality is to expand the provision of essential health and nutrition services to the country's rural poor. Health outcomes are slowly improving but remain low, particularly among rural dwellers and the very poor.